POWERFUL BUT DEATH IN ACTION: AN APPRAISAL OF UNITED NATIONS SECURITY COUNCIL RESPONSES TO RUSSO-UKRAINIAN WAR - Eyina, Nkatomba Nkatomba; Anyalebechi, Shammah Mahakwe (Journal of Social Science, 2025)
Objective: Accordingly, the study aimed to assess the effectiveness of the Security Council’s response to the Russo-Ukrainian War by examining its peacekeeping efficacy, decision-making processes, and enforcement of resolutions, thereby identifying strengths and weaknesses in these areas. Method: Anchored in a neorealist theoretical framework, the study adopted a qualitative design and employed content analysis to examine relevant United Nations documents and resolutions. Results: It found that the veto power of permanent members, especially when used by an involved party, paralyzed the Council’s decision-making and left its resolutions largely symbolic and unenforceable. The Responsibility to Protect (R2P) norm was effectively sidelined, as the Council failed to invoke it despite evidence of mass atrocities. Consequently, the Security Council proved ineffective in enforcing compliance with its decisions or altering the course of the conflict, demonstrating a significant gap between its mandate to maintain peace and its performance in this war. Novelty: Finally, it recommended curtailing the use of the veto in mass-atrocity situations, urging that permanent members abstain from vetoing in such cases to prevent Council paralysis and enable timely action.